Barriers to hepatitis C treatment in the era of direct‐acting anti‐viral agents. Issue 10 (26th September 2017) - Lin, M.; Kramer, J.; White, D.; Cao, Y.; Tavakoli‐Tabasi, S.; Madu, S.; Smith, D.; Asch, S. M.; El‐Serag, H. B.; Kanwal, F.
Summary: Background: Direct‐acting anti‐virals (DAA) are safe, effective treatment of hepatitis C virus (HCV). Suboptimal linkage to specialists and access to DAAs are the leading barriers to treatment; however, data are limited. Aim: To determine predictors of follow‐up, receipt of DAAs, and reasons for the lack thereof. Methods: We used clinical data from retrospective cohort of HCV‐infected patients with previously established HCV care in the US Department of Veterans Affairs to examine predictors of follow‐up in HCV clinics and DAA treatment (during 12/1/2013‐4/30/2015). We then conducted a structured review of medical charts of HCV patients to determine reasons for lack of follow‐up and treatment. Results: We identified 84 221 veterans who were previously seen in HCV clinics during the pre‐DAA era. Of these, 47 165 (56.0%) followed‐up in HCV specialty clinics, 13 532 (28.7%) of whom received DAAs. Older age, prior treatment, presence of cirrhosis or HCC, HIV/HBV co‐infection and psychiatric illness were predictors of follow‐up. Alcohol/drug abuse and medical co‐morbidity were predictors of lack of treatment. Of the 905 prospectively recruited patients, 56.2% patients had a specialist visit and 28% received DAAs. Common reasons for lack of follow‐up were relocation (n = 148, 37.4%) and missed/cancelled appointments (n = 63, 15.9%). Reasons for lack of treatment included waiting for newer therapy (n = 99, 38.8%), co‐morbidities (n = 66, 25.9%) and alcohol/drug abuse (n = 63, 24.7%). Conclusions: Half of patients with established HCV care were followed‐up in the DAA era and only 29% received DAAs. Targeted efforts focusing on patient and system‐levels may improve the reach of treatment with the new DAAs.